Roles of Key Actors in Intergenerational Transmission of Indigenous Knowledge within Tharu Community (Orchid Academia Siraha, 2024)
This study investigates roles of key actors in intergenerational transmission of indigenous knowledge (IK) within the Tharu community in Nepal. Employing basic qualitative research design within an interpretive paradigm, in-depth interviews were conducted with six Tharu teachers from three secondary schools in Jitpur-Simara sub-metropolitan city and focus group discussions with ten Tharu students chosen by using purposive sampling techniques, who were studying at Central Department of Education, Tribhuvan University. Findings reveal that parents, relatives, peers, priests, and journalists all play significant roles in imparting both indigenous knowledge within Tharu youngsters. Parents play crucial role for transferring practical skills, cultural traditions, and various roles to be executed in the community. Relatives provide supplementary knowledge, while peer interaction is crucial for socialization. Priests serve as keepers of spiritual and cultural knowledge, and journalists increasingly influence knowledge dissemination. The study concludes that IK transmission in the Tharu community is a multifaceted process involving various key actors.